Apa - Szabó, István (Hungary, 1966)
After his father is killed in World War II, a young Hungarian boy named Tako concocts a fantasy image of the parent he never really knew. Convincing himself of his father's unstinting bravery, the boy grows into a man who hopes to emulate his father’s heroism.
Keywords: Fiction films